Valuation techniques and financial statement disclosures for non-bearer plant sustainability performance in Indonesia / Widya Perwitasari … [et al.] - Perwitasari, Widya; Mohammed, Norazida; Sultan, Nasir; Mita, Aria Farah; Mahmud, Radziah (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
This study presents early evidence of the current valuation techniques and financial statement disclosure of non-bearer plants by companies on the Indonesia Stock Exchange. The emphasis is on measurement and valuation techniques amended in 2018-2019—the compliance in financial statement disclosure items provided by the companies. The valuation technique of a biological asset is quite challenging because this process includes measurements due to changes in market price and biological transformation. The study was conducted through a review of financial statements, primarily focusing on their disclosure. The study compared the change recorded in the initial years after amendments in accounting policy (2018 and 2019). The result showed that companies applied no uniform techniques to the valuation of biological assets. Therefore, it significantly affected their disclosure mainly due to the scarcity of technical guidance concerning biological assets. This study was limited to observing disclosure information and its accounting treatment by companies listed in Indonesian Stock Exchange under Agriculture and related industries. This study is useful to academics, accounting standard setters, and regulatory bodies. The paper is useful as feedback to accounting standard setters regarding implementing Financial Accounting Standard No.69: Agriculture in Indonesia. The findings aim to provide insights to regulatory bodies regarding financial information provided by companies in the logging sector.